Hill of Freedom - Hong Sang-soo; Park Hong-yeol; Kase, Ryo; Moon So-ri; Seo Young-hwa (Grasshopper Film, 2021)
Kwon (Seo Young-hwa) returns to Seoul from a restorative stay in the mountains. She is given a packet of letters left by Mori (Ryo Kase), who has come back from Japan to propose to her. As she walks down a flight of stairs, Kwon drops and scatters the letters, all of which are undated. When she reads them, she has to make sense of the chronology … and so must we. Shot in the narrow alleys, petite cafes and beautiful hanok inns of Seoul's historic Jong-ro district, a favorite Hong location, "Hill of Freedom" is a masterful, alternately funny and haunting, tale of love and longing from the great director. [Cover]